Challenges in applying scientific evidence to width recommendations for riparian management in agricultural Australia. (January 2015) - Hansen, Birgita D.; Reich, Paul; Cavagnaro, Timothy R.; Lake, P. S.
Summary Intact riparian zones maintain aquatic–terrestrial ecosystem function and ultimately, waterway health. Effective riparian management is a major step towards improving the condition of waterways and usually involves the creation of a 'buffer' by fencing off the stream and planting vegetation. Determination of buffer widths often reflects logistical constraints (e.g. private land ownership, existing infrastructure) of riparian and adjacent areas, rather than relying on rigorous science. We used published information to support riparian width recommendations for waterways in agricultural Victoria, Australia. We focused on different ecological management objectives (e.g. nutrient reduction or erosion control) and scrutinised the applicability of data across different environmental contexts (e.g. adjacent land use or geomorphology). Not surprisingly, the evidence supported variable 'effective' riparian widths, depending on the objective and environmental context. We used this information to develop a framework for determining riparian buffer widths to meet a variety of ecological objectives in south‐east Australia. Widths for reducing nutrient inputs to waterways were most strongly supported with quantitative evidence and varied between 20 and 38 m depending on environmental context. The environmental context was inconsistently reported, making it difficult to recommend appropriate widths, under different land‐use and physiographic scenarios. The evidence to guide width determination generally had high levels of uncertainty. Despite the considerable amount of published riparian research, there was insufficient evidence to demonstrate that implemented widths achieved ecological objectives. We emphasise the need for managers to clearly articulate the objectives of proposed riparian management and carefully consider the environmental context. Monitoring ecological responses associated with different riparian buffer widths is essential to support future management decisions.